Resistencia De Los Nematodos Gastrointestinales En Bovinos A Los Antihelmínticos Ivermectina Y Albendazol En Tres Fincas Del Municipio De Cabrera Cundinamarca - Alejo Cortes, Sebastian (Universidad Antonio Nariño, 2024)
As time went by, after large-scale beef production on the planet, increased the prevalence of gastrointestinal pathologies. Therefore, the increase in Pathology forced farmers and agricultural producers to choose development technologies, research and progress to control various diseases, especially against parasites.